The Effect of Terrorist Attack on Tourism Supply Chain in Gulshan and Dhaka - Sabiha Matin; Shafayet Mansoor (International Journal of Supply Chain Management, 2018)
The study has conducted the research on changes in activity behaviors of tourist in affected cities in Dhaka, Bangladesh. The reservations were cancelled after the Gulshan attack where five of the foreign guests checked in during this period. It is quite essential to inform the tourist police when any visitor arrives. The exploratory research design was employed in this study where the secondary research has been conducted for the purpose of other than the issue at hand. The study has conducted the secondary research which includes the data from reports and produces the output required for the current research study. According to the outcomes of the research study, government sits with the parties to address the extremism issues whereas almost 4,500 foreign tourists said that inbound tourism supply chain has been on the wane. The host expected almost 3000 to 4000 tourists in the year 2016 until 2017 and saw that there were cancellations after the two foreign nationals murder one was Japanese and other was Italian. The conclusion has demonstrated that Gulshan incident is a total disaster for the tourism supply chain.